In vivo evaluation of an adaptive resuscitation controller using whole blood and crystalloid infusates for hemorrhagic shock - Snider, Eric J.; Vega, Saul J.; Nessen, I. Amy; Hernandez Torres, Sofia I.; Salazar, Sophia; Berard, David; Salinas, Jose (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Hemorrhage remains the leading cause of preventable death on the battlefield. The most effective means to increase survivability is early hemorrhage control and fluid resuscitation. Unfortunately, fluid resuscitation requires constant adjustments to ensure the casualty is properly managed which is often not feasible in the pre-hospital setting. Here, we show how an adaptive closed-loop controller for hemorrhage resuscitation can be used to automate hemodynamic management using a swine hemorrhagic shock injury model.The adaptive resuscitation controller (ARC) was previously developed to track pressurevolume responsiveness in real-time and adjust its infusion rate to reach target mean arterial pressure (MAP). Swine were maintained under a surgical plane of anesthesia and underwent a splenectomy followed by two hemorrhage and resuscitation events. For the first resuscitation event, hemorrhage was induced to reduce MAP to 35 mmHg until arterial lactate reached 4 mmol/L. The ARC system then infused whole blood (WB) to target MAP and maintained the subject using crystalloid for 120 minutes. For the second resuscitation event, subjects were hemorrhaged again but resuscitated by ARC using only crystalloid infusion to target MAP and 120 minute maintenance.Results: ARC was effective at WB resuscitation, reaching target MAP in 2.0±1.0 minutes. Median performance error was 1.1±4.6% and target overshoot was 14.4±7.0% of target MAP. ARC was able to maintain swine for the maintenance period in all animals. For the second resuscitation, crystalloidbased resuscitation required longer to reach target MAP, at an average rise time of 4.3±4.0 minutes. However, target overshoot was reduced to 8.4±7.3% of target MAP. Much higher flow rates were required to maintain at target MAP after the second resuscitation event compared to the first.Discussion: ARC was able to rapidly reach and maintain target MAP effectively. However, this sometimes required large volumes of fluid as ARC's only goal was to reach target MAP. Further clinical insight is needed regarding the preferred aggression level to achieve target MAP. In conclusion, ARC was successful in vivo at its programmed objective of reaching and maintaining target MAP for extended periods of time, a critical next step toward improving hemorrhage treatment in the pre-hospital environment.